EVALUATION ON TRACKING PERFORMANCE OF NPID TRIPLE HYPERBOLIC AND NPID DOUBLE HYPERBOLIC CONTROLLER BASED ON FAST FOURIER TRANSFORM (FFT) FOR MACHINE TOOLS - Abdullah, L.; Junoh, S.C.K.; Salim, S.N.S.; Jamaludin, Z.; Chiew, T.H.; Anang, N.A.; Retas, Z.; Nordin, M.H. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Accuracy and precision are the area of interest in machine tools application. It is evaluated via the measurement of tracking performance of the controllers. This study presents a Fast Fourier Transform (FFT) technique that used to evaluate the tracking performance of two controllers, namely NPID Triple Hyperbolic controller and NPID Double Hyperbolic controller for XY Table Ball-screw driven system. The cutting force characteristics are observed by using a FFT technique. Peak amplitude of FFT error on harmonic frequency was observed as a cutting force occurrence on the control system. Two cutting force disturbances that are generated from spindle speed of 1500 rpm and 2500 rpm at frequency of 0.2 Hz of speed of motor were used as a configuration set up to compare the tracking performance between the two controllers. The average error reduction of FFT error at cutting force of 1500 rpm between NPID Double Hyperbolic and NPID Triple Hyperbolic was 25.12%. This average error reduction result showed that the NPID Double Hyperbolic controller produced better tracking performance compared to the other controller. For future work, it is recommended to explore the superiority features offered in artificial intelligence tool box for better judgment in tuning control parameters.